Quality of work organization and workers’ health from a gender perspective - Nicola MAGNAVITA (GIornale Italiano di Psicologia e Medicina del Lavoro, 2025)
The industrialization of the last century has posed the problem of defining the criteria for the organization of work. Two main models have confronted each other: the scientific organization of work or rationalization, and human factors. These two different orientations, through countless evolutions and contaminations, are still confronted in various productive sectors, including health. This study examines the relationships between work organization and health using three different methods of evaluating the organization and taking into account especially female workers, who are a vulnerable category. In the first survey, perceived organizational justice was found to be a significant predictor of physical and mental health. Women reported experiencing less interpersonal justice than men. In the second survey, poor quality of work organization reported by workers is associated with poor physical and mental health, with women suffering the greatest harm from poor organizational quality. In the third survey, intrusive leadership style and overtime work promote workaholism and cause damage to workers’ physical and mental health, which is greater in women. In conclusion, the study shows that workers’ health depends on work organization and that women suffer marked damage from inappropriate work organization.